Globalization or empire? - Nederveen Pieterse, Jan (Routledge, 2004)
Is America's cultural, economic and military domination of the world globalization, or is it just empire? In this smart, brief book, Pieterse confronts many of the most important issues surrounding this question.
Keywords: United States -- Foreign relations -- 2001-; Balance of power.; Imperialism.; United States -- Foreign economic relations.; Globalization -- Political aspects -- United States.; World politics -- 1989-; Équilibre des puissances.; Impérialisme.; Mondialisation -- Aspect politique -- États-Unis.; Politique mondiale -- 1989-; États-Unis -- Relations extérieures -- 2001-; États-Unis -- Relations économiques extérieures.; POLITICAL SCIENCE -- Government -- International.; POLITICAL SCIENCE -- International Relations -- General.; Balance of power; Globalization -- Political aspects; Imperialism; International economic relations; Diplomatic relations; World politics; United States; Imperialismus; Außenwirtschaftspolitik; Globalisierung; Außenpolitik; Gleichgewichtspolitik; USA; Internationalisatie.; Neoliberalisme.; Imperialisme.; Since 1989